2017
DOI: 10.1007/s00253-017-8394-2
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of Escherichia coli biofilm cells with different aspect ratios: a role of substratum material stiffness

Abstract: Bacterial biofilms play an important role in chronic infections due to high-level tolerance to antibiotics. Thus, it is important to eradicate bacterial cells that are attached to implanted medical devices of different materials. Phagocytosis is a key process of the innate immunity to eliminate invading pathogens. Previous research demonstrated that the efficiency of phagocytosis is affected by the aspect ratio of polymer beads. Recently, we reported that the stiffness of polydimethylsiloxane (PDMS) influences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Guegan [ 73 ] believed that the elastic modulus of agarose hydrogels could affect the formation of cell clusters of proteins adhering to bacterial cells. Yanrui et al [ 74 ] reported that the hardness of polydimethylsiloxane (PDMS) affected the formation of E. coli biofilms. They found that shorter E. coli cells were easier to engulf than longer cells isolated from the surface of soft PDMS.…”
Section: Relationship Between Dental Materials Surface Properties And...mentioning
confidence: 99%
“…Guegan [ 73 ] believed that the elastic modulus of agarose hydrogels could affect the formation of cell clusters of proteins adhering to bacterial cells. Yanrui et al [ 74 ] reported that the hardness of polydimethylsiloxane (PDMS) affected the formation of E. coli biofilms. They found that shorter E. coli cells were easier to engulf than longer cells isolated from the surface of soft PDMS.…”
Section: Relationship Between Dental Materials Surface Properties And...mentioning
confidence: 99%
“… 32,136 Recent studies have also gathered evidence that environmental stiffness can impact other factors relevant to bacterial disease. For instance, bacteria cultured on stiff substrates are more effectively removed by macrophages via phagocytosis 137 and are less susceptible to antibiotic treatments, 138 as compared to bacteria grown on soft substrates. In a recent study by Pierrat et al , the physical interactions between E. coli and human cells were examined.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“… 138 Here, bacteria invasion was correlated with the host cell's actin cytoskeleton: bacteria co-localized in regions of F-actin and high cell stress, which were more abundant on stiff substrates than soft substrates. Matrix stiffness has also been shown to regulate other host cell factors relevant to infection, such as the activity of macrophages 137 and the ability of antibiotics to accumulate inside the host cell to target bacteria. 138 …”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…The phagocytic index was performed as described previously. 36 The BMDMs were seeded in 24-well plates and exposed to 2.5 μg/ml EVs or PBS as a negative control overnight. Then, the FITC-expressing…”
Section: Phagocytosis Assaymentioning
confidence: 99%